THE INFLUENCE OF LEARNING MOTIVATION ON STUDENTS' LEARNING ACHIEVEMENT OF SDN 112 PEKANBARU - Muhammad Padli Nasution; Risnawati; Nasir Za'ba (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research aims to determine the picture of student learning motivation at SDN 112 Pekanbaru, to find out the picture of student learning achievement at SDN 112 Pekanbaru, to find out how much influence the learning motivation of students at SDN 112 Pekanbaru has. This research is quantitative, with a research population of all class V students at SDN 112 Pekanbaru, totaling 82 people. Determining the number of samples used saturated samples, thus the number of samples in this study was 82 people. The data collection techniques used are questionnaire techniques and observation techniques. The data analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The results of the research show that the description of students' learning motivation at SDN 112 Pekanbaru is in the high category, the description of students' learning achievement at SDN 112 Pekanbaru is in the quite high category, the influence of students' learning motivation at SDN 112 Pekanbaru is in the medium category.